2017
DOI: 10.1159/000479207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microRNA-135a on Cell Proliferation, Migration, Invasion, Apoptosis and Tumor Angiogenesis Through the IGF-1/PI3K/Akt Signaling Pathway in Non-Small Cell Lung Cancer

Abstract: Objective: This study explored the ability of microRNA-135a (miR-135a) to influence cell proliferation, migration, invasion, apoptosis and tumor angiogenesis through the IGF-1/PI3K/Akt signaling pathway in non-small cell lung cancer (NSCLC). Methods: NSCLC tissues and adjacent normal tissues were collected from 138 NSCLC patients. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the expression levels of miR-135a and IGF-1, PI3K, Akt, VEGF, bFGF and IL-8 mRNA; western blotting was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 41 publications
(48 reference statements)
1
79
0
Order By: Relevance
“…14 More than 50% of the miRNA genes have been located in tumor-related genomic regions or fragile sites. 28 Zhou's findings indicated that miR-135a promotes cell apoptosis and inhibits cell proliferation, migration, invasion, and tumor angiogenesis by targeting IGF-1 gene through the IGF-1/PI3K/Akt signaling pathway in NSCLC, 29 and MiR-135a inhibits migration and invasion and regulates EMT-related marker genes by targeting KLF8 in lung cancer cells, 30 which is consistent with our study, while Zhang's study showed that MiR-135a overexpression promoted viability, migration, and invasion, but inhibited apoptosis of NCI-H1650 and NCI-H1975 cells. The serum miR-135a level was downregulated in non-small-cell lung carcinoma (NSCLC) patients and was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 More than 50% of the miRNA genes have been located in tumor-related genomic regions or fragile sites. 28 Zhou's findings indicated that miR-135a promotes cell apoptosis and inhibits cell proliferation, migration, invasion, and tumor angiogenesis by targeting IGF-1 gene through the IGF-1/PI3K/Akt signaling pathway in NSCLC, 29 and MiR-135a inhibits migration and invasion and regulates EMT-related marker genes by targeting KLF8 in lung cancer cells, 30 which is consistent with our study, while Zhang's study showed that MiR-135a overexpression promoted viability, migration, and invasion, but inhibited apoptosis of NCI-H1650 and NCI-H1975 cells. The serum miR-135a level was downregulated in non-small-cell lung carcinoma (NSCLC) patients and was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the detailed mechanism of miR-21 in NSCLC cells, the PI3K/AKT and NF-κB signaling pathways were tested using miR-21 inhibitor. A number of studies showed that PI3K/AKT was involved in human lung cancer [30-33]. Previous studies identified activation of the PI3K/AKT pathway and observed it in human lung carcinomas [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the considerable advances in cancer surgery, chemotherapy, and molecular targeting therapies, the outcome of lung cancer patients remains poor. Invasion and migration of tumor cells are major challenges in the clinical treatment of NSCLC [5]. Consequently, the identification of novel molecules that inhibit the invasion and migration of lung cancer cells is imminent.…”
Section: Introductionmentioning
confidence: 99%